2018
DOI: 10.1155/2018/2785696
|View full text |Cite
|
Sign up to set email alerts
|

Role of Double-Carbapenem Regimen in the Treatment of Infections due to Carbapenemase Producing Carbapenem-Resistant Enterobacteriaceae: A Single-Center, Observational Study

Abstract: Purpose (i) To compare infections caused by carbapenem-susceptible (CS) and carbapenemase producing carbapenem-resistant Enterobacteriaceae (CP-CRE); (ii) to evaluate the clinical effectiveness of the double-carbapenem (DC) regimen in comparison with the best available treatment (BAT) in infections caused by CP-CRE; and (iii) to determine the exact minimal inhibitory concentrations (MICs) of meropenem/ertapenem (MEM/ETP) and the degree of in vitro ETP+MEM synergism in subjects receiving the DC. Methodology Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Although apparently paradoxical, the use of carbapenems in combinations with other agents for the treatment of carbapenem-resistant MDR-GNB was frequent in the past (before the availability of novel BL-BLI). This approach was based on the possibility of achieving sufficient carbapenem concentrations against some resistant organisms with only slightly increased carbapenem MICs, and also because of possible synergistic effects (2831). According to the results of large observational studies, this approach seemed ultimately favorable for severe CRE infections caused by KPC-producing strains, whereas a recent randomized, controlled trial (RCT) did not find differences in survival between meropenem plus colistin vs. colistin alone for the treatment of severe CRAB infections (10, 11, 32).…”
Section: Current Treatment Options For Mdr-gnb In Critically-ill Patimentioning
confidence: 99%
“…Although apparently paradoxical, the use of carbapenems in combinations with other agents for the treatment of carbapenem-resistant MDR-GNB was frequent in the past (before the availability of novel BL-BLI). This approach was based on the possibility of achieving sufficient carbapenem concentrations against some resistant organisms with only slightly increased carbapenem MICs, and also because of possible synergistic effects (2831). According to the results of large observational studies, this approach seemed ultimately favorable for severe CRE infections caused by KPC-producing strains, whereas a recent randomized, controlled trial (RCT) did not find differences in survival between meropenem plus colistin vs. colistin alone for the treatment of severe CRAB infections (10, 11, 32).…”
Section: Current Treatment Options For Mdr-gnb In Critically-ill Patimentioning
confidence: 99%
“…Actual therapeutic strategies are to increase the doses of carbapenem, colistin, and tigecycline or to combine these drugs. Double-carbapenem therapy was adopted as a salvage therapy for critically ill patients with CRE or CPE infections [ 19 , 20 ], but the evidence about this therapeutic option is low [ 21 , 22 ]. Ceftazidime/avibactam and ceftolozane/tazobactam could be useful in the management of carbapenem-sparing programs in settings with a high prevalence of ESBL-producing Enterobacterales and DTR Gram-negative infections.…”
Section: Discussionmentioning
confidence: 99%
“…The studies selected for inclusion were assessed for risk of bias and all included studies were determined to have a moderate risk of bias, with the exception of the study conducted by Gutierrez-Gutierrez et al, 2017, (20) (18,19,20,21,22,23,24). Similarly all included studies were determined to have a low risk of bias due to deviations from intended interventions and in bias due to classification of interventions (18,19,20,21,22,23,24). The study conducted by De Pascale et al, 2017 (18) was determined to have a moderate risk of bias due to missing data, all other included studies were determined to have a low risk of bias due to missing data (19,20,21,22,23,24).…”
Section: Risk Of Bias Assessment Of Included Studiesmentioning
confidence: 99%
“…Similarly all included studies were determined to have a low risk of bias due to deviations from intended interventions and in bias due to classification of interventions (18,19,20,21,22,23,24). The study conducted by De Pascale et al, 2017 (18) was determined to have a moderate risk of bias due to missing data, all other included studies were determined to have a low risk of bias due to missing data (19,20,21,22,23,24). In addition, all studies had low risk of bias in both measurements of outcomes and in selection of the reported result (18,19,20,21,22,23,24).…”
Section: Risk Of Bias Assessment Of Included Studiesmentioning
confidence: 99%